Deconvolution of synthetic mRNA expression: Nucleoside chemistry alters translatability - Hanieh Moradian; Marko Schwestka; Toralf Roch; Manfred Gossen (Wiley, 2024)
Abstract Recent technological advances in the production of in vitro transcribed messenger RNA (IVT‐mRNA) facilitate its clinical use as well as its application in basic research. In this regard, numerous chemical modifications, which are not naturally observed in endogenous mRNA, have been implemented primarily to address the issue of immunogenicity and improve its biological performance. However, recent findings suggested pronounced differences between expression levels of IVT‐mRNAs with different nucleoside modifications in transfected cells. Given the multistep process of IVT‐mRNA delivery and subsequent intracellular expression, it is unclear which step is influenced by IVT‐mRNA chemistry. Here, we deconvolute this process and show that the nucleoside modification does not interfere with complexation of carriers, their physicochemical properties, and extracellular stability, as exemplified by selected modifications. The immediate effect of mRNA chemistry on the efficiency of ribosomal protein synthesis as a contributor to differences in expression was quantified by in vitro cell‐free translation. Our results demonstrate that for the nucleoside modifications tested, translatability was the decisive step in determining overall protein production. Also of special importance for future work on rational selection of tailored synthetic mRNA chemistries, our findings set a workflow to identify potentially limiting, modification‐dependent steps in the complex delivery process.